2019
DOI: 10.17843/rpmesp.2019.361.4232
|View full text |Cite
|
Sign up to set email alerts
|

Infección por virus linfotrópico de células T humanas tipo 1 en pacientes con diagnóstico de tuberculosis multidrogorresistente

Abstract: Perú es uno de los países de las Américas que tiene una alta incidencia de tuberculosis (TB) (1) ; además, se estima que tiene una prevalencia de 2,5% de serología positiva 2018]. Disponible en: http://temas.sld.cu/dengue/2017/12/27/ manual-washington-de-especialidades-clinicas-enfermedadesinfecciosas/ 5. Alves A, Moura D, Spolti G. Co-infection with hepatitis A and leptospirosis in the Amazon region: report of two cases. Trop Gastroenterol. 2011;32(3):234-6. 6. Núñez-Garbín A, Espinoza-Figueroa J, Sihuincha-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In this study, it was observed that 33.33% of the individuals assessed presented HTLV/tuberculosis co-infection, as immunological alterations induced by HTLV-1 may precede a high susceptibility to tuberculosis (TB) co-infection [19]. The literature shows a higher prevalence of this co-infection, especially in countries endemic to both infections such as Brazil and Peru [20].…”
Section: Discussionmentioning
confidence: 92%
“…In this study, it was observed that 33.33% of the individuals assessed presented HTLV/tuberculosis co-infection, as immunological alterations induced by HTLV-1 may precede a high susceptibility to tuberculosis (TB) co-infection [19]. The literature shows a higher prevalence of this co-infection, especially in countries endemic to both infections such as Brazil and Peru [20].…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, the prevalence of HTLV-1 has been estimated between 1–2% of the Peruvian population [ 19 ]. The co-infection of HTLV-1 with TB has been estimated between 2.8% to 5.6% among drug-susceptible and multidrug-resistant TB, respectively [ 13 , 20 ]. Few studies have characterized the lung lesions of HTLV-1 infected patients amongst those without known TB history.…”
Section: Introductionmentioning
confidence: 99%